2017
DOI: 10.3389/fneur.2017.00090
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cervical Vestibular-Evoked Myogenic Potential in Children with Attention Deficit and Hyperactivity Disorder

Abstract: ObjectiveEmerging evidence suggests that children with attention deficit and hyperactivity disorder (ADHD) present more difficulties in standing and walking balance than typically developing children. Most of previous studies have assessed these functions using postural and sensory organization tests showing differences in balance performance between control and ADHD children. However, to date, it is unknown whether these balance alterations are accompanied with vestibular dysfunction. The principal aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…Further, prevalence rates are growing for diagnoses that characteristically involve sensory integration and praxis difficulties. For example, diagnoses of attention deficit disorders with and without hyperactivity are on the rise [109], and at least one study indicates that vestibular processing challenges, previously unidentified in this population, may affect some children with this diagnosis [110]. Sensory integration and praxis concerns, including atypical reactivity, are prevalent among children with autism [45,54].…”
Section: Discussionmentioning
confidence: 99%
“…Further, prevalence rates are growing for diagnoses that characteristically involve sensory integration and praxis difficulties. For example, diagnoses of attention deficit disorders with and without hyperactivity are on the rise [109], and at least one study indicates that vestibular processing challenges, previously unidentified in this population, may affect some children with this diagnosis [110]. Sensory integration and praxis concerns, including atypical reactivity, are prevalent among children with autism [45,54].…”
Section: Discussionmentioning
confidence: 99%
“…A difference from controls in VEMP testing can additionally be used to support diagnoses which perhaps have no obvious relation to balance and dizziness, or to each other. These include brainstem lesions ( Oh et al, 2013 ), multiple scleroris ( Escorihuela García et al, 2013 ; Gabelić et al, 2013 ; Ivanković et al, 2013 ; Güven et al, 2014 ), dementia ( Harun et al, 2016 ), Parkinson’s disease ( Shalash et al, 2017 ) and attention deficit and hyperactivity disorder ( Isaac et al, 2017 ). See Oh et al (2016) or Deriu et al (2019) for further review and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Note also that Deroualle and Lopez [ 32 ] reported several behavioral and neuroimaging studies suggesting the vestibular contribution to emotional and social cognition. Furthermore, Isaac et al [ 33 ] reported reduced cVEMPs (cervical vestibular evoked myogenic potentials) amplitudes or a total lack of responses in children with ADHD, suggesting the presence of peripheral and central vestibular impairments in these children. Note that, even if cervical and ocular VEMPs have mostly been related to peripheral vestibular disorders, the characteristics and the diagnostic values of VEMPs have been used to assess the function of the central otolithic pathways; indeed, the cervical VEMPs are mediated by vestibular nuclei and uncrossed medial vestibulospinal tract descending in the lower brainstem and spinal cord [ 34 ].…”
Section: Discussionmentioning
confidence: 99%